Experimental and theoretical analysis of mechanical draft counterflow wet cooling towers - ONAT, AYHAN (TAYLOR & FRANCIS INC, 2020)
Wet cooling towers have high thermal efficiency and are cost-effective industrial cooling units, used in factories, in energy plants, and in the HVAC market. The working principle of the cooling towers is based on cooling of the hot process water with cold atmospheric air via cooling fills and water distribution systems. This study investigates the pressure losses and thermal performance of mechanical draft counterflow water cooling towers having different cooling fill heights. During the thermal performance tests, the pressure loss through cooling fill was separately measured for each condition. The variation of pressure losses with air velocity was plotted through cooling fills at different loading heights. Performance curves were obtained and compared as graphs relating the liquid-gas ratio (L/G) to the Merkel number for cooling fills at different heights between 1500 mm and 2400 mm. Although the lowest and the highest flow resistances were measured at fill heights of 1500 mm and 2400 mm, the lowest and the highest performances for the cooling tower were calculated at 1500 mm and 2400 mm, respectively.